Dialogisme, discours familiaux et apprentissage du français en classe - Florence Guiraud (Recherches en didactique des langues et des cultures)
Our purpose in this article is to study language production in a school environment for young migrants learning French as a foreign language. To analyze the discourse of these learners, the theoretical framework of dialogism appears operative in particular in its interdiscursive dimension. Indeed, the observation of the discursive materiality of their utterances at the microsyntactic level reveals the recurrent use of specific syntactic construction. For the interlocutor-receiver the utterance of the learner sometimes implies another perceptible voice through what might resemble syntactic construction errors As a matter of fact their utterances belong to an interlinguistic space which seems managed by dialogism. We will hereby focus on the specific use of deictic pronouns and verbal tenses. We will see that the dialogic context such as defined by Bakhtine-Volochinov (1929-1977) may enable us to formulate hypotheses and explanations as to what might be considered incorrect use of the language.